Mechanical activation of ultramafic mine waste rock in dry condition for enhanced mineral carbonation. (September 2016) - Li, Jiajie; Hitch, Michael
Highlights: Serpentine is partially dehydrated and converted to olivine by intensive dry grinding. Serpentine content enhances the formation of new surface during mechanical activation. Serpentine content reduces the disorder of microstructure in olivine during grinding. 3600 kW h/t energy input can improve the carbonation conversion from 8.7% to 31.7%. Abstract: This study examines mechanical activation as the pre-treatment method for ultramafic mine waste containing olivine and serpentine. Specific surface area, microstructure and carbonation conversion in a direct aqueous carbonation process were measured to test the effects of mechanical activation. It was found that, as a result of the grinding energy input on materials, surface area was increased, crystallite size was reduced and microstrain was accumulated, carbonation conversion was enhanced. With the presence of serpentine content, the formation of new surface area was promoted and the disordering of forsterite structure was prevented. Forsterite makes up the majority of the content and contributes to CO2 sequestration under selected carbonation conditions. For the purposes of mineral carbonation, the mechanical activation of mine waste is preferable to simply grinding pure olivine.